Enhanced Intelligent Model for NCD in Wireless Sensor Networks - Thaile, Manyam; Ramanaiah, O.B.V. (Discoveries in Agriculture and Food Sciences, 2018)
The serious security threat for Wireless Sensor Network comes from compromised nodes. Node Compromise (NC) effects of two types: independent and dependent. In independent type, the NC effect is limited to that node only; whereas in dependent, it will spread to all the nodes across the network. In literature, there is an intelligent model which predicts the spread of node compromise. This model suffers from false positives as it trusts the communication from neighbouring nodes. To address this issue, our Parameter Grouping (PG) † mechanism is used in association with the existing Intelligent Model (IM). This Extended Intelligent Model (E-IM) performs better than the IM. The E-IM has studied through NS-2 based simulation and its performance is analyzed.